Satellite Monitoring for Forest Management : Use of Earth Observation Tools in the Monitoring of Tropical Dry Forests - World Bank (World Bank, Washington, DC, 2021)
This briefing note presents some recent developments in satellite-based earth observation (EO) and how new and disruptive technology can improve understanding on tropical dry forests. It focuses on tools and algorithms developed by the Satellite Monitoring for Forest Management (SMFM) project financed by the Global Environment Facility (GEF) and implemented by the World Bank in 2017–2020. This note summarizes the key aspects on using satellite data in dry forest monitoring and its target audience is senior forest managers, policy makers and other users of forest data. For more technology focused audience, the SMFM project also prepared a series of other documents: i) good practice guidance – a guidance document for dry forest assessment and monitoring; ii) validation compliance report; iii) project implementation summary; and iv) working practice document (manual) for each tool developed under the project.